Determination of Aqueous Two‐Phase System Binodals and Tie‐Lines by Electrowetting‐on‐Dielectric Droplet Manipulation. (13th December 2018) - Kojima, Taisuke; Lin, Chu‐Chi; Takayama, Shuichi; Fan, Shih‐Kang
Abstract: Handling the aqueous two‐phase systems (ATPSs) formed by liquid–liquid phase separation (LLPS) relies on the accurate construction of binodal curves and tie‐lines, which delineate the polymer concentrations required for phase separation and depict the properties of the resulting phases, respectively. Various techniques to determine the binodal curves and tie‐lines of ATPSs exist, but most rely on manually pipetting relatively large volumes of fluids in a slow and tedious manner. We describe a method to determine ATPS binodals and tie‐lines that overcomes these disadvantages: microscale droplet manipulation by electrowetting‐on‐dielectric (EWOD). EWOD enables automated handling of droplets in an optically transparent platform that allows for in situ droplet observation. Separated phases are clearly visible, and the volumes of each phase are readily determined. Additionally, in considering the molecular crowding present in living cells, this work examines the role of a macromolecule in prompting LLPS. These results show that EWOD‐driven droplet manipulation effectively interrogates the phase dynamics of ATPSs and macromolecular crowding in LLPS. Abstract : Not phased out : EWOD‐enabled droplet manipulation integrated with ATPSs quantifies the phase dynamics of various ATPS solutions. In situ observation of droplets in the presence of background macromolecules reveals macromolecular crowding effects on the phase dynamics and can potentially interrogate the physiological liquid–liquid phase separation prevalent in living cells.